GENEALOGI ILMU TARBIYAH DAN PENDIDIKAN ISLAM: Studi Kritis terhadap Masa Pertumbuhan - Rama, Bahaking (Inspiratif Pendidikan, 2016)
The discussion of Genealogy of the science of Tarbiyah and Islamic Education dealing with its growth and development can be traced from Prophet Mohammed’s period. Genealogy of the science of Tarbiyah as a scientific foundation of Islamic Education was rooted in the first Revelation recieved by Prophet Muhammad showing the importance of education. The word Iqra’اقرا) ) shows the activity of reading; the word al-Qalam (القلم) suggests the importance of educational means and technologies for writing activities, and the word maalam ya’lam (مالم يعلم ) indicates the object in education (students) and the need for an educator. Then, the history of Islamic education showed that Prophet Muhammad pays high attention to education. He always held a study (ta’lim) to his friends in order to make them understand the Islamic teachings universally. He designed a complex study, Dar al-Arqam (educational institutions). The Badr war prisoners who can read and write can be released if they can teach to read and write to at least 10 Muslim children (the eradication of illiteracy). Furthermore, At its development, Islamic education is seen during Khulafah Al-Rasyidin with maintaining the characteristic as Prophet Muhammad periode even though every change of leadership was marked by several significant developments. To uncover the history of Islamic education development during the Khulafah Al-Rashidun, it should be approached gradually in accordance with the leadership of the caliphate period (Abubakar-As-Siddiq, Umar Bin Khattab, Uthman Bin Affan, and Ali Bin Abi Talib).